Integrasi Pelayanan Teman Bus Terhadap Kawasan Strategis Pariwisata Nasional di Bali - Verina Dwiyolanda Ginting; I Kadek Krisnanda Putra; Ni Putu Anistia Maharani; Rizal Arzi Fajar Kusuma; Arif Devi Dwipayana (Universitas Jember, 2022)
The transportation service integration system aims to facilitate transportation users in carrying out activities. One factor that determines the integration of transportation services is the route.